Teachers as transformative intellectuals: Democracy in the classroom - osman, ahmed abdikadir (Advances in Social Sciences Research Journal, 2015)
Abstract Democracy in education is the rights of the teachers to teach truthfully and employ their reason to the full extent of their intellectual powers. It is the freedom of professionally qualified persons to inquire, discover, publish and teach as they see it in their field of competence, without any control or authority of rational methods by which truth is established. Democracy is essential to the fulfillment of the purpose of the school. Teachers should be protected from censorship or restraint that unreasonably interferes with their obligation to expose students to controversial issues and to help students express their own views on such issues. The teacher’s responsibility should be to show objectivity to see that various sides of controversial issues are given. To carry out this responsibility the teacher should be well informed in the areas being studied. It’s recognized that every teacher has the right to a point of view and to express that view, but the teacher has the responsibility to tell the students that the statement is a personal view. Key words: Freedom, democracy, censorship, education, liberation, dialogue